Sands of Time
XVI, 359 p. 149 illus., 115 illus. in color.
Keywords: This monograph presents the results of over 10 years of paleontological and geological survey in the Baynunah Formation of the United Arab Emirates. Exposed widely in western Abu Dhabi Emirate, the Baynunah Formation and its fossils provide the only record of terrestrial environments and evolution in the Arabian Peninsula during the late Miocene epoch (12-5 Ma). This volume describes new fossils collected since 2002, presented systematically by taxon, and including mammals, reptiles, and invertebrates, as well as fossil trackways. The discoveries are framed within the results of new geological, geochemical, and geochrononological analyses, providing an updated and synthetic view of the age, environments, and biogeographic relationships of this important fossil assemblage.